Towards a hybrid semantic similarity measure to set the conceptual relatedness in a hierarchy. (2016) - Nessah, Djamel; Kazar, Okba; Benharkat, AÁ¯cha-Nabila
Assessment of semantic similarity between concepts is of great importance in many applications dealing with textual data, such as natural language processing, knowledge acquisition, document semantic annotation and information retrieval systems. Moreover, to extract similar concepts from multiple ontologies, there is a real need to develop a conceptual similarity measure, the intention of finding semantic similarity in a given hierarchy, is to enhance the integration and retrieval of heterogeneous information resources in a more meaningful and accurate way. In this paper we present a hybrid approach for measuring the semantic similarity, in an attempt to address a new issue that focuses on the sensitivity of the similarity measure between concepts in a hierarchy. Based on the notions of both distance and the information content, the measure is expected to provide more consistent and accurate measures.